Perversion and Perpetration in Female Genital Mutilation Law: The Unmaking of Women as Bearers of Law. (April 2020) - Pardy, Maree; Rogers, Juliet; Seuffert, Nan
Female genital cutting (FGC) or, more controversially, female genital mutilation, has motivated the implementation of legislation in many English-speaking countries, the product of emotive images and arguments that obscure the realities of the practices of FGC and the complexity of the role of the practitioner. In Australia, state and territory legislation was followed, in 2015, with a conviction in New South Wales highlighting the problem with laws that speak to fantasies of 'mutilation'. This article analyses the positioning of Islamic women as victims of their culture, represented as performing their roles as vehicles for demonic possession, unable to authorize agency or law. Through a perverse framing of 'mutilation', and in the case through the interpretation of the term 'mutilation', practices of FGC as law performed by women are obscured, avoiding the challenge of a real multiculturalism that recognises lawful practices of migrant cultures in democratic countries.